Same-Sex Marriage, Toleration, and the Clergy of the Finnish Lutheran Church - Laura Kallatsa (Religions, 2022)
In this study, I clarify what kind of attitudes the clergy of the Evangelical Lutheran Church of Finland (ELCF) have towards same-sex marriage and how they treat people who disagree with them. The empirical research material consists of 534 answers from Finnish clergy. The ELCF has rejected same-sex marriages, while in all other Nordic countries, the Lutheran churches are marrying same-sex couples. However, over half of the Finnish Lutheran clergy support same-sex marriages in the church. My article shows that the main justifications for their attitudes are: (1) theological justifications, (2) legal justifications, and (3) justifications related to the essence of marriage. Most of the priests treated respectfully those who disagree with them, while a third of the priests had negative thoughts. As a background theory I use the Theory of Moral Foundations, which gives useful tools for understanding why the clergy are divided by same-sex marriage.